CHARACTERISTICS OF MIRNA INTERACTION WITH 5’UTR, CDS, 3’UTR MRNA CANDIDATE GENES OF METABOLIC SYNDROME DISEASE (Experimental biology, 2019)
Studying of the pathogenesis of metabolic syndrome is one of the most topical because of the widespread of this pathology. The study of genetic nature of cardiovascular diseases is one of the most promising areas of molecular medicine worldwide. Identification of a group of individual genetic markers allows early diagnosis and optimization of primary and secondary prevention of metabolic syndrome. Therefore, the process of biomarkers discovery should improve the therapy and assessment of the risk of cardiovascular disease. The search for effective markers is the subject of ongoing research. The miRNAs interaction with mRNAs of candidate genes were predicted using the MirTarget program. The genes responsible for the development of metabolic syndrome, regulated by miRNAs were selected by searching in the PubMed database. ADRA2A and SCAP genes are regulated by 12 and 15 miRNAs through 5'UTR with the highest binding energy is -144 kJ/mole and -151 kJ/mole, respectively. AR, CEBPA, IGFBP2, KL and SIRT1 genes are regulated through CDS by 7, 19, 11, 13 and 6 miRNAs, with the highest binding energy is -134 kJ / mole, -142 kJ/mole, -140 kJ/mole, -142 kJ/mole and -138 kJ/mole, respectively. Clusters of miRNA binding sites with overlapping nucleotide sequences were detected in mRNA of several genes. Several associations of miRNA and genes are proposed as biomarkers for developing methods for diagnosing the metabolic syndrome.Key words: miRNA, mRNA, metabolic syndrome, candidate genes.